The Pedagogical Use of Gamification in English Vocabulary Training and Learning in Higher Education - Benjamin Panmei; Budi Waluyo (MDPI AG, 2022)
One of the persistent challenges in vocabulary teaching is that EFL students must learn a certain number of words to operate in English, yet class time is limited. While the usage of gamification applications may alleviate some of these issues, research on the usefulness of gamification apps and their potential to assist student vocabulary learning outside of the classroom is currently limited. This study used a quasi-experimental method to investigate the effects of gamified vocabulary learning using an application called Quizizz. It compared the learning outcomes of experimental and control groups, as well as the usefulness of gamification in boosting learner autonomy in vocabulary learning. Multiple independent t-tests revealed non-significant differences between students' overall vocabulary test results in both groups (t (2, 98) = 1.920, p = 0.06) with a modest effect size (Cohen's d = 0.3). Significant differences were noticed in the results of vocabulary tests 2 (t (2, 98) = 3.229, p = 0.002) and 4 (t (2, 98) = 3.465, p = 0.001), where the students in the experimental groups achieved higher scores (M = 13.63 and M = 12.60), yet no significant differences were noted in the results of vocabulary tests 1 and 2. Significant changes occurred in students' perceptions of the application of gamification as a means for facilitating training (t (1, 49) = 2.269, p = 0.03) with a modest effect size (Cohen's d = 0.2). Nonetheless, their perceptions of the use of gamification for enhancing learner autonomy in vocabulary learning did not significantly change before and after the interventions (t (1, 49) = 1.652, p = 1.05) with a very small effect size (Cohen's d = 0.2). For pedagogy and research, the findings enhance our understanding that gamification apps can be integrated into vocabulary learning to facilitate vocabulary study and foster the growth of learner autonomy, yet utilizing a non-specifically built app for vocabulary learning may not produce better results than those who do not receive gamification support, even if learning outcomes remain good. More research exploring the impacts of integrating a non-specifically built app into English language teaching and learning is needed.